2022
DOI: 10.3389/fnins.2022.1005810
|View full text |Cite
|
Sign up to set email alerts
|

High-precision neural stimulation by a highly efficient candle soot fiber optoacoustic emitter

Abstract: Highly precise neuromodulation with a high efficacy poses great importance in neuroscience. Here we developed a candle soot fiber optoacoustic emitter (CSFOE), capable of generating a high pressure of over 10 MPa with a central frequency of 12.8 MHz, enabling highly efficient neuromodulation in vitro. The design of the fiber optoacoustic emitter, including the choice of the material and the thickness of the layered structure, was optimized in both simulations and experiments. The optoacoustic conversion effici… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Under the laser condition of 45 µJ per pulse, the FE produced an ultrasound waveform with a peak-to-peak pressure of over 8 MPa ( Fig. 1b ), which is consistent with previously published results and is sufficient for efficient PA neurostimulation 20 . When coupled with the CW laser, the FE functions as a pure PT source and generates a very localized thermal field ( Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Under the laser condition of 45 µJ per pulse, the FE produced an ultrasound waveform with a peak-to-peak pressure of over 8 MPa ( Fig. 1b ), which is consistent with previously published results and is sufficient for efficient PA neurostimulation 20 . When coupled with the CW laser, the FE functions as a pure PT source and generates a very localized thermal field ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…We also performed mCherry temperature measurements under PA conditions. Based on previously reported studies 20 , the PA signal generated by a burst of nanosecond pulsed laser of 3 ms is sufficient to activate neurons. Here, maintaining the average laser power at 120 mW, the same as the PT laser condition, a pulse train (1030 nm, 3 ns, RPMC, Fallon, MO, USA) of 3 ms duration was applied to the FE and the fluorescence intensity of mCherry was monitored ( Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…[43,44] Recently, our work showed that fiber-based optoacoustic emitters can also be applied to neural stimulation in vitro and in vivo, with single neuron resolution and dual site capability. [39,45] In these studies, typically commercial silica fibers were used, together with optoacoustic coating. However, the silica fiber, with Young's modulus of approximately70 GPa, is mismatched with mechanical properties of native neural tissue (kilo-to mega pascals) [2] and not easy to integrate with miniaturized electrodes for recording.…”
Section: Design Fabrication and Characterization Of Mfoementioning
confidence: 99%
“…144 A number of photoacoustic converters based on optical fibres have been developed for neuro-modulation. 142,143,235 Cheng's team reported a miniaturized fibre-optoacoustic converter (FOC) for neuro-modulation at submillimeter spatial precision. 142 The FOC tip is coated with a nanocomposite, which is composed of an absorption layer (graphite/epoxy) and a diffusion layer (ZnO NPs/epoxy).…”
Section: Light-driven Indirect Acoustic Stimulation Through Lightabso...mentioning
confidence: 99%